Break any woman down : stories - Johnson, Dana, 1967- (Flannery O'Connor Award for Short Fiction., 2001)
In Break Any Woman Down, Dana Johnson explores race, identity, and alienation with unflinching honesty and vibrant language. Hip and seductive, her stories often feature women discovering their identities through sexual and emotional intimacy with the men in their lives." "In the title story, La Donna is a black stripper whose white boyfriend, an actor in adult movies, insists that she stop stripping. In "Melvin in the Sixth Grade," eleven-year-old Avery has a crush on a white boy from Oklahoma who, like Avery, is an outsider in their suburban Los Angeles school. "Markers" is as much about a woman's relationship with her mother as it is about the dissolution of her relationship with an older Italian man